2019
DOI: 10.1002/pen.25051
|View full text |Cite
|
Sign up to set email alerts
|

Oil‐impregnated monomer casting nylon composites reinforced by graphene oxide and Lanthanum(III) chloride

Abstract: Oil‐impregnated monomer casting (OMC) nylon composites reinforced by graphene oxide and Lanthanum(III) chloride (LaCl3) were prepared by anionic ring‐opening polymerization in the presence of sodium hydroxide catalyst and toluene‐2, 4‐diisocyanate cocatalyst. The cross‐linked GO was formed by the coordination and electrostatic interactions between La3+ and the carboxyl on the edge of GO, which resulted in an obvious reinforcement for the OMC nylon composites. The effects of different rare earth contents on mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The elastic modulus, flexural strength, flexural modulus, compressive strength, notched impact strength, and elongation‐at‐break for the OMC nylon/GO/LaCl 3 composites were increased by 6.1%, 9.9%, 18.2%, 7.2%, 40.8%, and 24.4%, respectively, and the tensile strength was slightly improved. [ 22 ] Furthermore, Xu et al prepared monomer casting (MC) nylon‐6/SiO 2 composites via in situ polymerization. It was found that the tensile strength, storage modulus, and notched Charpy impact strength of the composites were improved and reached maxima at 3–5 wt% SiO 2.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic modulus, flexural strength, flexural modulus, compressive strength, notched impact strength, and elongation‐at‐break for the OMC nylon/GO/LaCl 3 composites were increased by 6.1%, 9.9%, 18.2%, 7.2%, 40.8%, and 24.4%, respectively, and the tensile strength was slightly improved. [ 22 ] Furthermore, Xu et al prepared monomer casting (MC) nylon‐6/SiO 2 composites via in situ polymerization. It was found that the tensile strength, storage modulus, and notched Charpy impact strength of the composites were improved and reached maxima at 3–5 wt% SiO 2.…”
Section: Introductionmentioning
confidence: 99%